2011
DOI: 10.1111/j.1538-7836.2010.04109.x
|View full text |Cite
|
Sign up to set email alerts
|

The prothrombin time/international normalized ratio (PT/INR) Line: derivation of local INR with commercial thromboplastins and coagulometers – two independent studies

Abstract: Summary. Background: The WHO scheme for prothrombin time (PT) standardization has been limited in application, because of its difficulties in implementation, particularly the need for mandatory manual PT testing and for local provision of thromboplastin international reference preparations (IRP). Methods: The value of a new simpler procedure to derive international normalized ratio (INR), the PT/INR Line, based on only five European Concerted Action on Anticoagulation (ECAA) calibrant plasmas certified by expe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…1,2 There is no need for local manual PT testing using the World Health Organization (WHO) thromboplastin international reference preparations (IRPs) required in the conventional WHO method for international sensitivity index (ISI) calibration to obtain INRs. 3 The PT/ INR Line is a development of the "direct INR" method of Houbouyan and Goguel, 4 later modified in the Scientific and Standardization Committee Guidelines and in the Clinical and Laboratory Standards Institute document, 5,6 that gave discouraging results in a previous European Concerted Action on Anticoagulation (ECAA) study.…”
Section: The Prothrombin Time/international Normalized Ratio (Pt/inr)mentioning
confidence: 99%
“…1,2 There is no need for local manual PT testing using the World Health Organization (WHO) thromboplastin international reference preparations (IRPs) required in the conventional WHO method for international sensitivity index (ISI) calibration to obtain INRs. 3 The PT/ INR Line is a development of the "direct INR" method of Houbouyan and Goguel, 4 later modified in the Scientific and Standardization Committee Guidelines and in the Clinical and Laboratory Standards Institute document, 5,6 that gave discouraging results in a previous European Concerted Action on Anticoagulation (ECAA) study.…”
Section: The Prothrombin Time/international Normalized Ratio (Pt/inr)mentioning
confidence: 99%
“…As variable INR values in the same plasma sample could be obtained on different coagulometers, ISI calibration of all routinely used reagents is very important ( 9 ). This survey showed that most respondents use PT reagents derived from human placenta and rabbit brain although recombinant tissue factor reagents have better sensitivity to factor deficiencies and plasma samples from patients treated with OAT ( 10 ).…”
Section: Discussionmentioning
confidence: 99%
“…The INR is based on ISI values derived from plasma of patients on stable warfarin doses for more than 6 weeks. The INR values determined with warfarintreated patients are transferred for patients treated with other coumarin derivatives [1][2][3]. Rivaroxaban binds competitively and reversibly to free factor Xa and to factor Xa bound in the prothrombinase complex.…”
Section: Interference Of Anticoagulants On Coagu Lation Assays and Mementioning
confidence: 99%